Pedagogical Experiments On The Development Of Professional Competencies Of Students Based On An Integrative Approach And Their Results - Ismoilov Elmurod Olloberdi o‘g‘li (Periodica Journal, 2022)
The article presents the results of pedagogical experiments on the development of professional competencies of students on the basis of an integrative approach. The questions and assignments used in pedagogical experiments and their essence are described. Based on the conducted pedagogical experiments and the results recorded in them, teachers were recommended to teach students mathematics and specialized disciplines on the basis of an integrated approach in the formation of professional competencies.
Keywords: competence; professional competence; integration; integrative approach